A composite material for self-sensing robotic arms of embodied drones and a method of manufacturing the same
Patent Information
- Application Number
- CN202611307538.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]具身无人机自感知机臂作为整机核心承力部件,既要承受电机振动、飞行弯矩与冲击载荷,同时还面临复杂的电磁环境,机臂内部及周边布置有电调、驱动、信号传输器件,易受到外界电磁干扰,也会产生电磁辐射,影响机载设备工作稳定性
[0044](1)本发明汇总CNF/PEDOT导电传感层嵌入机臂结构内部,使机臂本身成为应变传感器,无需外贴应变片,消除了贴片脱胶和布线复杂的问题,整机重量减轻5%~8%。
Smart Images

Figure CN123001273A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of high-performance composite materials, specifically, it relates to a composite material for a self-sensing arm of a self-contained unmanned aerial vehicle and its preparation method. Background Technology
[0002] As a core load-bearing component of the embodied drone, the self-sensing arm must withstand motor vibration, flight bending moments, and impact loads, while also facing a complex electromagnetic environment. The arm's internal and surrounding areas house electronic speed controllers, drives, and signal transmission devices, making it susceptible to external electromagnetic interference and generating electromagnetic radiation, which can affect the operational stability of onboard equipment. Current drone arms are mostly made of carbon fiber epoxy resin composite materials, focusing on mechanical load-bearing performance and offering relatively limited functionality. They typically rely on external strain gauges for structural health monitoring and adhered metal shielding films for electromagnetic protection, making it difficult to simultaneously meet the multiple requirements of load-bearing capacity, conductive sensing, and electromagnetic shielding.
[0003] Traditional external strain gauges are bonded to the surface of the robotic arm. The adhesive layer is susceptible to vibration and temperature / humidity cycles, resulting in a high detection limit, difficulty in capturing minute deformations, and susceptibility to electromagnetic interference, leading to decreased measurement reliability. Metal shielding films add significant weight, have poor interfacial bonding with the substrate, and are prone to warping and detachment during service, making it impossible to achieve integrated molding with the load-bearing structure. While introducing conductive fillers directly into the resin matrix to construct a conductive network can impart conductivity and electromagnetic shielding to the robotic arm, excessive filler doping can increase internal defects in the composite material, leading to poor interfacial bonding, decreased mechanical strength and modulus, and ultimately reduced load-bearing capacity. It is difficult to achieve a synergistic balance between conductive sensing, electromagnetic shielding, and structural load-bearing capacity.
[0004] Therefore, developing a composite material for the arm that combines lightweight design, efficient electromagnetic compatibility shielding, stable electrical conductivity and thermal management, and high load-bearing strength has become a critical technological bottleneck that needs to be overcome in the field of UAV materials. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to extend the service life of drones by wrapping the base surface of the drone arm with a composite material consisting of a biochar electromagnetic shielding layer, a CNF / PEDOT conductive sensing layer, and a CS-CF structural support layer.
[0006] To achieve the above objectives, the present invention discloses the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite material for a self-sensing arm of an embodied unmanned aerial vehicle, comprising the following steps:
[0008] (1) Preparation of CS-CF structural bearing layer
[0009] (1.1) Add urea and cellulose to sodium hydroxide aqueous solution at a mass ratio of 2.5-3.5:1, and control the mass concentration of cellulose in the system to be 8-12%; stir and dissolve at a temperature of -8~-2℃ for 3.5-4.5h to obtain cellulose spinning solution;
[0010] (1.2) The cellulose spinning solution is extruded into the coagulation bath through a spinneret, and the raw fiber is obtained after coagulation;
[0011] (1.3) The precursor fiber is pre-oxidized in air by heating to 240-280℃ at 1-3℃ / min and holding for 40-50min; then carbonized in nitrogen protection by heating to 800-900℃ at 3-7℃ / min and holding for 10-20min to obtain CS-CF precursor fiber.
[0012] (1.4) The CS-CF precursor fibers are impregnated with a resin matrix and woven into a unidirectional fabric, then cured to obtain the CS-CF structural bearing layer;
[0013] (2) Fabrication of CNF / PEDOT conductive sensing layer
[0014] (2.1) Cellulose was oxidized by TEMPO and then homogenized under high pressure to obtain CNF dispersion;
[0015] (2.2) Mix PEDOT:PSS aqueous solution and CNF dispersion at a mass ratio of 4-6:1, add silane coupling agent, mix, and obtain composite conductive coating solution;
[0016] (2.3) The composite conductive coating liquid is coated on the surface of the CS-CF structure carrier layer, pre-cured at 90~110℃ for 10-20min, and then cured at 130~150℃ for 45min to obtain CNF / PEDOT conductive sensing layer.
[0017] (3) Preparation of biochar electromagnetic shielding layer
[0018] A biochar electromagnetic shielding layer was prepared by mixing biochar powder and epoxy resin in a mass ratio of 15~30:70~85.
[0019] (4) The CNF / PEDOT conductive sensing layer and the biochar electromagnetic shielding layer are stacked in sequence, placed in a vacuum bag and cured by hot pressing to obtain a composite material for the self-sensing arm of the unibody UAV.
[0020] Preferably, in step (1.4), the raw materials of the resin matrix, by weight, include 90-110 parts of mixed epoxy resin, 8-12 parts of DOPO flame retardant, and 27-33 parts of lignin-based curing agent. The resin content of the unidirectional fabric is 33-37%, and the areal density is 190-210 g / m². The curing process involves placing the unidirectional fabric in a vacuum bag, evacuating it, sealing it, and then placing it in an autoclave. The temperature is increased to 140-160°C at a rate of 1-3°C / min, while the pressure is increased to 0.5-0.7 MPa. The temperature and pressure are maintained for 80-100 min. Subsequently, the temperature is decreased to 60°C at a rate of 0.7-1.5°C / min, and the pressure is released from the autoclave.
[0021] More preferably, the mixed epoxy resin is epoxy resin E-51 and epoxy resin F-51 in a mass ratio of 60~80:20~40.
[0022] Preferably, in step (2.1), the TEMPO oxidation is performed using sodium hypochlorite as the oxidant, the amount of sodium hypochlorite is 3-7 mmol / g, the pressure of the high-pressure homogenization treatment is 75-85 MPa, the number of treatments is 2-4, and the solid content of the CNF dispersion is 1.8-2.2%.
[0023] More preferably, the CNF dispersion contains cellulose with a diameter of 20-40 nm and an aspect ratio >10.
[0024] Preferably, in step (2.2), the silane coupling agent is KH-560, the dosage is 0.8-1.2%, and the mixing is performed by ultrasonication at 300-400W for 40-50 minutes.
[0025] Preferably, in step (2.3), the coating thickness of the composite conductive coating liquid is 80-150 μm.
[0026] More preferably, in step (2.3), the CS-CF structure bearing layer is pre-embedded with electrode leads, and the electrode leads are arranged at equal intervals along the arm axis with a spacing of 50~150mm.
[0027] More preferably, the electrode leads are copper foil mesh or silver paste printed electrodes, and the electrode width is 2~5mm.
[0028] Preferably, in step (3), the method for preparing the biochar powder includes the following steps:
[0029] S1: Gasify cotton stalks at 780-850℃ for 55-65 minutes to obtain crude biochar;
[0030] S2: The crude biochar was ball-milled using zirconia balls as the milling medium at a ball-to-material ratio of 8-12:1, a milling speed of 280-320 rpm, and a milling time of 1.5-2.5 h. The powder with a particle size of 20-40 μm was obtained by passing it through a 400-mesh sieve and modifying it with KH-560 silane coupling agent to obtain biochar powder.
[0031] In this invention, biochar powder is prepared from cotton stalks. After a series of treatments such as gasification, ball milling and modification with silane coupling agent, the powder with a preferred particle size of 20~40μm is not only controlled to have a specific surface area of about 850m² / g, which is beneficial to improve electromagnetic shielding absorption loss, but also improves the dispersion effect of biochar powder in resin.
[0032] Preferably, in step (3), the raw material of the biochar electromagnetic shielding layer further includes 20-30% amine curing agent based on the weight of epoxy resin. The mixing is carried out by mixing the raw material of the biochar electromagnetic shielding layer by planetary stirring. The vacuum degree of the planetary stirring is -0.08~-0.1MPa, the rotation speed is 50-70rpm, and the stirring time is 20-40min.
[0033] More preferably, the amine curing agent is at least one of aliphatic amines, cycloaliphatic amines, polyamides, or polyether amines.
[0034] More preferably, the amine curing agent is a polyetheramine curing agent.
[0035] Preferably, the thickness of the biochar electromagnetic shielding layer is 200~300μm.
[0036] Preferably, the preparation method of the lignin-based curing agent includes the following steps:
[0037] A1: Phenolicizing lignin to obtain phenolized lignin. The conditions for the phenolicizing reaction are: a mass ratio of phenol to lignin of 2-4:1, a molar ratio of formaldehyde to phenol of 0.5-1.0:1, oxalic acid or hydrochloric acid as the catalyst, a reaction temperature of 70-90℃, and a reaction time of 2-4h.
[0038] A2: Phenolic lignin is dissolved in N,N-dimethylformamide, DOPO, formaldehyde and catalyst are added, and the mixture is stirred and mixed at 100~140℃ for 3~6h to obtain a reaction solution. The reaction solution is added to deionized water to precipitate, filtered, washed with water and vacuum dried to obtain a lignin-based curing agent.
[0039] More preferably, the ratio of phenolic lignin to N,N-dimethylformamide in the liquid solution is 1g:4-6mL, the mass ratio of DOPO flame retardant to phenolic lignin is 0.4-0.8:1, the molar ratio of formaldehyde to DOPO flame retardant is 1.0-2.0:1, the catalyst is triethylamine or sodium hydroxide, and the amount of catalyst used is 1%-3% of the total mass of the reactants.
[0040] In this invention, lignin is first phenolized and then reacted with DOPO flame retardant to obtain a curing agent containing a lignin skeleton, phenolic hydroxyl groups, and DOPO phosphorus-containing groups. By introducing a phosphonate structure, on the one hand, the interface is stabilized through chemical grafting with cellulose hydroxyl groups via POC covalent bonds; on the other hand, the strong polarity of the phosphorus-containing groups generates dipole interactions with the resin matrix, enhancing interfacial compatibility. The rigid aromatic ring network of the lignin skeleton provides structural support, and the abundant active sites (phenolic hydroxyl groups, carboxyl groups) on the molecular chain can form a dense hydrogen bond network with cellulose hydroxyl groups, enhancing interfacial wettability. At the same time, its polymer chain entanglement effect can alleviate the resin curing shrinkage stress and improve the stability of the composite material.
[0041] More preferably, the preparation method of the lignin is as follows: cotton stalks are used as raw materials, and after steam explosion at 1.5 MPa for 5 minutes, they are subjected to alkali-oxygen treatment. The alkali-oxygen treatment involves soaking in a solution containing 8% NaOH and 2% hydrogen peroxide at 80°C for 2 hours, followed by filtration to obtain a filtrate. The pH of the filtrate is adjusted to 2.0 with a 2 mol / L hydrochloric acid solution, and cotton stalk lignin is precipitated. After washing with water until neutral and drying, the finished product is obtained.
[0042] Preferably, in step (4), the curing process is as follows: vacuum degree ≤ -0.095MPa, heating rate of 1~2℃ / min to 120~150℃, curing pressure 0.3~0.6MPa, and heat and pressure holding for 60~120min.
[0043] The beneficial effects of this invention are:
[0044] (1) The present invention integrates CNF / PEDOT conductive sensing layer embedded inside the arm structure, so that the arm itself becomes a strain sensor, eliminating the need for external strain gauges, eliminating the problems of adhesive peeling and complex wiring, and reducing the weight of the whole machine by 5%~8%.
[0045] (2) High sensitivity micro-strain detection: The high aspect ratio of CNF and the conductive network of PEDOT:PSS work together to make the strain sensitivity coefficient GF≥10 of the conductive sensing layer, which can detect micro-strain of 0.1%, meeting the deformation monitoring requirements of UAV arm under aerodynamic load.
[0046] (3) Global strain field reconstruction: By arranging multiple pairs of electrode leads along the arm axis and combining them with the inverse finite element method iFEM, the global strain field of the arm can be reconstructed from the resistance changes of discrete measurement points, thus realizing the leap from 'point measurement' to 'field sensing'.
[0047] (4) Built-in electromagnetic shielding: The biochar electromagnetic shielding layer is integrated into the inner wall of the arm. The shielding effectiveness is ≥30dB in the 8~18GHz frequency band, effectively isolating electromagnetic interference from the motor, protecting the flight control system and communication module, and eliminating the need for an external metal shielding cover. Attached Figure Description
[0048] Figure 1 SEM morphology of CNF / PEDOT conductive sensing layer in Example 3
[0049] Figure 2 SEM image of the cross-section of the biochar electromagnetic shielding layer in Example 3
[0050] Figure 3 SEM image of the overall cross-section of the composite material in Example 3 Detailed Implementation
[0051] Those skilled in the art can refer to the content of this document to appropriately improve the process parameters. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in this invention.
[0052] The products and methods of the present invention have been described through preferred embodiments. Those skilled in the art will be able to make modifications or appropriate alterations and combinations to the products and methods described herein without departing from the content, spirit and scope of the present invention, so as to realize and apply the technology of the present invention.
[0053] Experimental methods in the following examples, unless otherwise specified, are generally performed under standard conditions or as recommended by the manufacturer. Materials, reagents, etc., used are commercially available unless otherwise specified. Unless otherwise stated, substances described in this invention are calculated as percentages and parts by mass.
[0054]
[0055] The preparation methods for lignin and cellulose are as follows: Cotton stalks are used as raw material and subjected to steam explosion at 1.5 MPa for 5 minutes, followed by alkali-oxygen treatment. The alkali-oxygen treatment involves soaking the stalks in a solution containing 8% NaOH and 2% hydrogen peroxide at 80°C for 2 hours with a solid-liquid ratio of 1:10. The filtrate is then filtered. The pH of the filtrate is adjusted to 2.0 with 2 mol / L hydrochloric acid solution, precipitating cotton stalk lignin. This lignin is then washed with water until neutral and dried to obtain lignin. The filter cake is washed with deionized water to obtain cellulose.
[0056] Example 1
[0057] Preparation of lignin curing agent:
[0058] (1.1) Phenol and lignin were added to a three-necked flask at a mass ratio of 2:1, and formaldehyde and oxalic acid were added and mixed. The mixture was reacted at 70°C for 2 hours to obtain phenolic lignin. The molar ratio of formaldehyde to phenol was 0.5:1, and the amount of oxalic acid added was 4% based on the mass of lignin.
[0059] (1.2) Phenolic lignin was dissolved in N,N-dimethylformamide at a ratio of 1 g:4 mL. DOPO flame retardant, formaldehyde, and triethylamine were added, and the mixture was stirred and mixed at 100℃ for 3 h to obtain a reaction solution. The reaction solution was added to deionized water to precipitate the precipitate, filtered, washed with water, and vacuum dried to obtain a lignin-based curing agent. The ratio of phenolic lignin to N,N-dimethylformamide was 1 g:4 mL, the mass ratio of DOPO flame retardant to phenolic lignin was 0.4:1, the molar ratio of formaldehyde to DOPO flame retardant was 1.0:1, and the amount of triethylamine was 1% of the total mass of the reactants.
[0060] Preparation of biochar powder:
[0061] (1.1) Cotton stalks were gasified at 780℃ for 55 min to obtain crude biochar;
[0062] (1.2) The crude biochar was subjected to planetary ball milling with zirconia balls as the milling medium at a ball-to-material ratio of 8:1, a milling speed of 280 rpm, and a milling time of 1.5 h. The powder with a particle size range of 20-40 μm was obtained by passing it through a 400-mesh sieve. The powder was dried at 100 °C for 3 h, cooled, and then fed into a high-speed mixer. High-speed stirring was started and the temperature was preheated to 85 °C. 1% of KH-560 silane coupling agent by weight of powder was continuously added to the high-speed mixer by atomization spraying. The mixture was stirred at 1200 r / min for 8 min. The powder temperature was then maintained at 90 °C for 20 min. After stirring and cooling to room temperature, the mixture was discharged and sieved to obtain biochar powder.
[0063] Preparation of CS-CF precursor fibers
[0064] (1.1) Urea and cellulose were added to an 8wt% NaOH aqueous solution at a mass ratio of 2.5:1, and the mass concentration of cellulose in the system was controlled to be 8%; the solution was stirred and dissolved at -8℃ for 3.5h to obtain the cellulose spinning solution;
[0065] (1.2) The cellulose spinning solution is extruded into the coagulation bath through a spinneret and coagulated to obtain the precursor fiber. The spinneret has an orifice diameter of 0.08 mm and 1000 orifices. The coagulation bath is a mixed aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12%, the mass fraction of sodium sulfate is 18%, and the remainder is deionized water. The temperature of the coagulation bath is 15℃.
[0066] (1.3) The precursor fiber was pre-oxidized in air by heating to 240℃ at 1℃ / min and holding for 40min; then carbonized in nitrogen protection by heating to 800℃ at 3℃ / min and holding for 10min to obtain CS-CF precursor fiber.
[0067] Preparation of CNF dispersion
[0068] Cellulose was dispersed in deionized water and stirred to form a cellulose suspension. TEMPO and sodium bromide were added to the suspension and stirred continuously to dissolve. Sodium hypochlorite aqueous solution was slowly added dropwise under stirring conditions, with the amount of sodium hypochlorite added being 3 mmol / g based on cellulose, the amount of TEMPO added being 0.1 mmol / g based on cellulose, and the amount of sodium bromide added being 1 mmol / g based on cellulose. During the oxidation reaction, the pH of the system was maintained at 10.0 in real time using 0.5 mol / L sodium hydroxide solution, and the oxidation reaction was carried out under stirring at room temperature. After the reaction was completed, anhydrous ethanol was added to quench the remaining sodium hypochlorite and terminate the oxidation reaction. The material was centrifuged and repeatedly washed with deionized water to obtain TEMPO cellulose. TEMPO cellulose was subjected to high-pressure homogenization twice at a pressure of 75-85 MPa to obtain a CNF dispersion with a diameter of 20-40 nm, an aspect ratio >100, and a solid content of 1.8%.
[0069] Preparation of the CS-CF structural bearing layer
[0070] CS-CF precursor fibers were impregnated with a resin matrix and woven into unidirectional fabric. Six sheets of unidirectional fabric were stacked and placed in a vacuum bag, vacuumed, sealed, and then placed in an autoclave. The temperature was increased to 140°C at a rate of 1°C / min, while the pressure was increased to 0.5 MPa and held at that temperature and pressure for 80 minutes. Subsequently, the temperature was reduced to 60°C at a rate of 0.7°C / min, the pressure was released, and the fabric was removed from the autoclave for curing, thus obtaining the CS-CF structural load-bearing layer. The resin matrix, by weight, consisted of 90 parts of mixed epoxy resin, 8 parts of DOPO flame retardant, and 27 parts of lignin-based curing agent. The mixed epoxy resin was epoxy resin E-51 and epoxy resin F-51 in a mass ratio of 60:40. The resin content of the unidirectional fabric was 33%, and the areal density was 190 g / m².
[0071] Fabrication of CNF / PEDOT conductive sensing layer
[0072] (1.1) PEDOT:PSS aqueous solution and CNF dispersion were mixed at a mass ratio of 4:1. 0.8% KH-560 silane coupling agent was added based on the mass of the mixture. The mixture was sonicated at 300W for 40 min to obtain a composite conductive coating solution.
[0073] (1.2) Copper foil electrodes (3 mm wide and 0.05 mm thick) are pre-embedded in the CS-CF structure carrier layer at equal intervals (100 mm) along the axial direction of the arm. The two ends of the electrodes are led out to the connector at the root of the arm. Then, the composite conductive coating liquid is applied to the CS-CF structure carrier layer with a thickness of 80 μm. It is pre-cured at 90℃ for 10 min and then cured at 130℃ for 45 min to obtain the CNF / PEDOT conductive sensing layer.
[0074] Preparation of biochar electromagnetic shielding layer
[0075] Biochar powder and epoxy resin E-51 were mixed at a mass ratio of 15:85. 20% polyetheramine curing agent was added based on the weight of epoxy resin E-51. The mixture was prepared by planetary stirring with a vacuum of -0.08 MPa, a speed of 50 rpm, and a stirring time of 20 min. The resulting biochar electromagnetic shielding layer was then obtained.
[0076] Preparation of the self-sensing arm of the embodied drone
[0077] A CNF / PEDOT conductive sensing layer, a biochar electromagnetic shielding layer, and an imide film liner were sequentially wrapped around the surface of a mold. The mold was then placed in a vacuum bag, evacuated to -0.098 MPa, and placed in an autoclave for curing. The curing process involved heating to 120°C at a rate of 1°C / min, maintaining the temperature and pressure at 0.3 MPa for 60 minutes, followed by cooling to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer was 200 μm thick.
[0078] Example 2
[0079] Preparation of lignin curing agent:
[0080] (1.1) Phenol and lignin were added to a three-necked flask at a mass ratio of 4:1, and formaldehyde and oxalic acid were added and mixed. The mixture was reacted at 90°C for 4 hours to obtain phenolic lignin. The molar ratio of formaldehyde to phenol was 1.0:1, and the amount of oxalic acid added was 4% based on the mass of lignin.
[0081] (1.2) Phenolic lignin was dissolved in N,N-dimethylformamide at a ratio of 1 g:6 mL. DOPO flame retardant, formaldehyde, and triethylamine were added, and the mixture was stirred and mixed at 140℃ for 6 h to obtain a reaction solution. The reaction solution was added to deionized water to precipitate the precipitate, filtered, washed with water, and vacuum dried to obtain a lignin-based curing agent. The ratio of phenolic lignin to N,N-dimethylformamide was 1 g:6 mL, the mass ratio of DOPO flame retardant to phenolic lignin was 0.8:1, the molar ratio of formaldehyde to DOPO flame retardant was 2.0:1, and the amount of triethylamine was 3% of the total mass of the reactants.
[0082] Preparation of biochar powder:
[0083] (1.1) Cotton stalks were gasified at 850℃ for 65 min to obtain crude biochar;
[0084] (1.2) The crude biochar was subjected to planetary ball milling with zirconia balls as the milling medium at a ball-to-material ratio of 12:1, a milling speed of 320 rpm, and a milling time of 2.5 h. The powder with a particle size range of 20-40 μm was obtained by passing it through a 400-mesh sieve. The powder was dried at 100℃ for 3 h, cooled, and then fed into a high-speed mixer. High-speed stirring was started and the temperature was preheated to 85℃. 1% of KH-560 silane coupling agent by weight of powder was continuously added to the high-speed mixer by atomization spraying. The mixture was stirred at 1400 r / min for 12 min. The powder temperature was then maintained at 90℃ for 20 min. After stirring and cooling to room temperature, the mixture was discharged and sieved to obtain biochar powder.
[0085] Preparation of CS-CF precursor fibers
[0086] (1.1) Urea and cellulose were added to an 8wt% NaOH aqueous solution at a mass ratio of 3.5:1, and the mass concentration of cellulose in the system was controlled to be 12%; the solution was stirred and dissolved at -2℃ for 4.5h to obtain the cellulose spinning solution;
[0087] (1.2) The cellulose spinning solution is extruded into the coagulation bath through a spinneret and coagulated to obtain the precursor fiber. The spinneret has an orifice diameter of 0.08 mm and 1000 orifices. The coagulation bath is a mixed aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12%, the mass fraction of sodium sulfate is 18%, and the remainder is deionized water. The temperature of the coagulation bath is 15℃.
[0088] (1.3) The precursor fiber was pre-oxidized in air by heating to 280℃ at 3℃ / min and holding for 50min; then carbonized in nitrogen protection by heating to 900℃ at 7℃ / min and holding for 20min to obtain CS-CF precursor fiber.
[0089] Preparation of CNF dispersion
[0090] Cellulose was dispersed in deionized water and stirred to form a cellulose suspension. TEMPO and sodium bromide were added to the suspension and stirred continuously to dissolve. Sodium hypochlorite aqueous solution was slowly added dropwise under stirring conditions, with the amount of sodium hypochlorite added being 7 mmol / g based on cellulose, the amount of TEMPO added being 0.2 mmol / g based on cellulose, and the amount of sodium bromide added being 2 mmol / g based on cellulose. During the oxidation reaction, the pH of the system was maintained at 10.5 in real time using 0.5 mol / L sodium hydroxide solution, and the oxidation reaction was carried out under stirring at room temperature. After the reaction was completed, anhydrous ethanol was added to quench the remaining sodium hypochlorite and terminate the oxidation reaction. The material was centrifuged and repeatedly washed with deionized water to obtain TEMPO cellulose. TEMPO cellulose was subjected to high-pressure homogenization four times at a pressure of 85 MPa to obtain a CNF dispersion with a diameter of 20-40 nm, an aspect ratio >100, and a solid content of 2.2%.
[0091] Preparation of the CS-CF structural bearing layer
[0092] CS-CF precursor fibers were impregnated with a resin matrix and woven into unidirectional fabric. Six sheets of unidirectional fabric were stacked and placed in a vacuum bag, vacuumed, sealed, and then placed in an autoclave. The temperature was increased to 160°C at 3°C / min, and the pressure was increased to 0.7 MPa, and held at this temperature and pressure for 100 min. Subsequently, the temperature was decreased to 60°C at 1.5°C / min, the pressure was released, and the fabric was removed from the autoclave for curing, thus obtaining the CS-CF structural load-bearing layer. The resin matrix, by weight, consisted of 110 parts of mixed epoxy resin, 12 parts of DOPO flame retardant, and 33 parts of lignin-based curing agent. The mixed epoxy resin was epoxy resin E-51 and epoxy resin F-51 in a mass ratio of 80:20. The resin content of the unidirectional fabric was 37%, and the areal density was 210 g / m².
[0093] Fabrication of CNF / PEDOT conductive sensing layer
[0094] (1.1) PEDOT:PSS aqueous solution and CNF dispersion were mixed at a mass ratio of 6:1. 1.2% KH-560 silane coupling agent was added based on the mass of the mixture. The mixture was sonicated at 400W for 50 min to obtain a composite conductive coating solution.
[0095] (1.2) Copper foil electrodes (3 mm wide and 0.05 mm thick) are pre-embedded in the CS-CF structure carrier layer at equal intervals (100 mm) along the axial direction of the arm. The two ends of the electrodes are led out to the connector at the root of the arm. Then, the composite conductive coating liquid is applied to the CS-CF structure carrier layer with a thickness of 150 μm. It is pre-cured at 110℃ for 20 min and then cured at 150℃ for 45 min to obtain the CNF / PEDOT conductive sensing layer.
[0096] Preparation of biochar electromagnetic shielding layer
[0097] Biochar powder and epoxy resin E-51 were mixed at a mass ratio of 30:70. 30% polyetheramine curing agent was added based on the weight of epoxy resin E-51. The mixture was prepared by planetary stirring with a vacuum of -0.1 MPa, a speed of 70 rpm, and a stirring time of 40 min. The resulting biochar electromagnetic shielding layer was then obtained.
[0098] Preparation of the self-sensing arm of the embodied drone
[0099] A CNF / PEDOT conductive sensing layer, a biochar electromagnetic shielding layer, and an imide film liner were sequentially wrapped around the surface of a mold. The mold was then placed in a vacuum bag, evacuated to -0.098 MPa, and placed in an autoclave for curing. The curing process involved heating to 150°C at a rate of 2°C / min, curing at 0.6 MPa, holding at that temperature and pressure for 120 min, followed by cooling to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer was 300 μm thick.
[0100] Example 3
[0101] Preparation of lignin curing agent:
[0102] (1.1) Phenol and lignin were added to a three-necked flask at a mass ratio of 3:1, and formaldehyde and oxalic acid were added and mixed. The mixture was reacted at 80°C for 3 hours to obtain phenolic lignin. The molar ratio of formaldehyde to phenol was 0.8:1, the catalyst was oxalic acid, and the amount of catalyst was 4% of the mass of lignin.
[0103] (1.2) Phenolic lignin was dissolved in N,N-dimethylformamide at a ratio of 1 g:5 mL. DOPO flame retardant, formaldehyde, and triethylamine were added, and the mixture was stirred and mixed at 120℃ for 4 h to obtain a reaction solution. The reaction solution was added to deionized water to precipitate the precipitate, filtered, washed with water, and vacuum dried to obtain a lignin-based curing agent. The ratio of phenolic lignin to N,N-dimethylformamide was 1 g:5 mL, the mass ratio of DOPO flame retardant to phenolic lignin was 0.6:1, the molar ratio of formaldehyde to DOPO flame retardant was 1.5:1, and the amount of triethylamine was 2% of the total mass of the reactants.
[0104] Preparation of biochar powder:
[0105] (1.1) Cotton stalks were gasified at 800℃ for 60 min to obtain crude biochar;
[0106] (1.2) The crude biochar was subjected to planetary ball milling with zirconia balls as the milling medium at a ball-to-material ratio of 10:1, a milling speed of 300 rpm, and a milling time of 2 h. The powder with a particle size range of 20-40 μm was obtained by passing it through a 400-mesh sieve. The powder was dried at 100℃ for 3 h, cooled, and then fed into a high-speed mixer. High-speed stirring was started and the temperature was preheated to 85℃. 1% of KH-560 silane coupling agent by weight of powder was continuously added to the high-speed mixer by atomization spraying. The mixture was stirred at 1300 r / min for 10 min. The powder temperature was then maintained at 90℃ for 20 min. After stirring and cooling to room temperature, the mixture was discharged and sieved to obtain biochar powder.
[0107] Preparation of CS-CF precursor fibers
[0108] (1.1) Urea and cellulose were added to an 8wt% NaOH aqueous solution at a mass ratio of 3:1, and the mass concentration of cellulose in the system was controlled to be 10%; the solution was stirred and dissolved at -6℃ for 4h to obtain the cellulose spinning solution;
[0109] (1.2) The cellulose spinning solution is extruded into the coagulation bath through a spinneret and coagulated to obtain the precursor fiber. The spinneret has an orifice diameter of 0.08 mm and 1000 orifices. The coagulation bath is a mixed aqueous solution of sulfuric acid and sodium sulfate, wherein the mass fraction of sulfuric acid is 12%, the mass fraction of sodium sulfate is 18%, and the remainder is deionized water. The temperature of the coagulation bath is 15℃.
[0110] (1.3) The precursor fiber was pre-oxidized in air by heating to 260℃ at 2℃ / min and holding for 45min; then carbonized in nitrogen protection by heating to 850℃ at 5℃ / min and holding for 15min to obtain CS-CF precursor fiber.
[0111] Preparation of CNF dispersion
[0112] Cellulose was dispersed in deionized water and stirred to form a cellulose suspension. TEMPO and sodium bromide were added to the suspension and stirred continuously to dissolve them. Sodium hypochlorite aqueous solution was slowly added dropwise under stirring conditions, with the amount of sodium hypochlorite added being 5 mmol / g based on cellulose, the amount of TEMPO added being 0.15 mmol / g based on cellulose, and the amount of sodium bromide added being 1.5 mmol / g based on cellulose. During the oxidation reaction, the pH of the system was maintained at 10.3 in real time using 0.5 mol / L sodium hydroxide solution, and the oxidation reaction was carried out under stirring at room temperature. After the reaction was completed, anhydrous ethanol was added to quench the remaining sodium hypochlorite and terminate the oxidation reaction. The material was centrifuged and repeatedly washed with deionized water to obtain TEMPO cellulose. TEMPO cellulose was subjected to high-pressure homogenization three times at a pressure of 80 MPa to obtain a CNF dispersion with a diameter of 20-40 nm, an aspect ratio >100, and a solid content of 2%.
[0113] Preparation of the CS-CF structural bearing layer
[0114] CS-CF precursor fibers were impregnated with a resin matrix and woven into unidirectional fabric. Six sheets of unidirectional fabric were stacked and placed in a vacuum bag, vacuumed, sealed, and then placed in an autoclave. The temperature was increased to 150°C at a rate of 2°C / min, while the pressure was increased to 0.6 MPa, and the temperature and pressure were maintained for 90 minutes. Subsequently, the temperature was decreased to 60°C at a rate of 1°C / min, the pressure was released, and the fabric was removed from the autoclave for curing, thus obtaining the CS-CF structural load-bearing layer. The resin matrix, by weight, consisted of 100 parts of mixed epoxy resin, 10 parts of DOPO flame retardant, and 30 parts of lignin-based curing agent. The mixed epoxy resin was epoxy resin E-51 and epoxy resin F-51 in a mass ratio of 70:30. The resin content of the unidirectional fabric was 35%, and the areal density was 200 g / m².
[0115] Fabrication of CNF / PEDOT conductive sensing layer
[0116] (1.1) PEDOT:PSS aqueous solution and CNF dispersion were mixed at a mass ratio of 5:1. 1% KH-560 silane coupling agent was added based on the mass of the mixture. The mixture was sonicated at 350W for 45 min to obtain a composite conductive coating solution.
[0117] (1.2) Copper foil electrodes (3 mm wide and 0.05 mm thick) are pre-embedded in the CS-CF structure carrier layer at equal intervals (100 mm) along the axial direction of the arm. The two ends of the electrodes are led out to the connector at the root of the arm. Then, the composite conductive coating liquid is applied to the CS-CF structure carrier layer with a thickness of 130 μm. It is pre-cured at 100℃ for 15 min and then cured at 140℃ for 45 min to obtain the CNF / PEDOT conductive sensing layer.
[0118] Preparation of biochar electromagnetic shielding layer
[0119] Biochar powder and epoxy resin E-51 were mixed at a mass ratio of 20:80. 25% polyetheramine curing agent was added based on the weight of epoxy resin E-51. The mixture was prepared by planetary stirring with a vacuum of -0.09 MPa, a speed of 60 rpm, and a stirring time of 30 min. The resulting biochar electromagnetic shielding layer was then obtained.
[0120] Preparation of the self-sensing arm of the embodied drone
[0121] A CNF / PEDOT conductive sensing layer, a biochar electromagnetic shielding layer, and an imide film liner were sequentially wrapped around the surface of a mold, placed in a vacuum bag, and evacuated to -0.098 MPa before being placed in an autoclave for curing. The curing process involved heating to 130°C at a rate of 1.5°C / min, curing at a pressure of 0.4 MPa, holding at that temperature and pressure for 90 min, followed by cooling to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer had a thickness of 250 μm.
[0122] Comparative Example 1
[0123] Based on Example 3, the preparation method of the self-sensing arm of the embodied UAV is adjusted as follows:
[0124] A biochar electromagnetic shielding layer, a CNF / PEDOT conductive sensing layer, and an imide film liner were sequentially wrapped around the surface of a mold. The mold was then placed in a vacuum bag, evacuated to -0.098 MPa, and placed in an autoclave for curing. The curing process involved heating to 130°C at a rate of 1.5°C / min, maintaining the temperature and pressure at 0.4 MPa for 90 minutes, followed by cooling to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer had a thickness of 250 μm.
[0125] Comparative Example 2
[0126] Based on Example 3, the thickness of the biochar electromagnetic shielding layer was adjusted, specifically as follows:
[0127] A CNF / PEDOT conductive sensing layer, a biochar electromagnetic shielding layer, and an imide film liner were sequentially wrapped around the surface of a mold, placed in a vacuum bag, and evacuated to -0.098 MPa before being placed in an autoclave for curing. The curing process was as follows: the temperature was increased to 130°C at a rate of 1.5°C / min, the curing pressure was 0.4 MPa, and the temperature and pressure were maintained for 90 min. Subsequently, the temperature was decreased to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer had a thickness of 150 μm.
[0128] Comparative Example 3
[0129] Based on Example 3, the thickness of the biochar electromagnetic shielding layer was adjusted, specifically as follows:
[0130] A CNF / PEDOT conductive sensing layer, a biochar electromagnetic shielding layer, and an imide film liner were sequentially wrapped around the surface of a mold. The mold was then placed in a vacuum bag, evacuated to -0.098 MPa, and placed in an autoclave for curing. The curing process involved heating to 130°C at a rate of 1.5°C / min, maintaining the temperature and pressure at 0.4 MPa for 90 minutes, followed by cooling to 60°C at a rate of 1°C / min before removal from the autoclave and demolding to obtain the self-sensing robotic arm. The biochar electromagnetic shielding layer had a thickness of 350 μm.
[0131] Comparative Example 4
[0132] Based on Example 3, the preparation method of the CNF / PEDOT conductive sensing layer is adjusted as follows:
[0133] (1.1) PEDOT:PSS aqueous solution and CNF dispersion were mixed at a mass ratio of 5:1. 1% KH-560 silane coupling agent was added based on the mass of the mixture. The mixture was sonicated at 350W for 45 min to obtain a composite conductive coating solution.
[0134] (1.2) Copper foil electrodes (3 mm wide and 0.05 mm thick) are pre-embedded in the CS-CF structure carrier layer at equal intervals (100 mm) along the axial direction of the arm. The two ends of the electrodes are led out to the connector at the root of the arm. Then, the composite conductive coating liquid is applied to the CS-CF structure carrier layer with a thickness of 250 μm. It is pre-cured at 100℃ for 15 min and then cured at 140℃ for 45 min to obtain the CNF / PEDOT conductive sensing layer.
[0135] Comparative Example 5
[0136] Based on Example 3, the preparation method of the CNF / PEDOT conductive sensing layer is adjusted as follows:
[0137] (1.3) PEDOT:PSS aqueous solution and CNF dispersion were mixed at a mass ratio of 5:1. 1% KH-560 silane coupling agent was added based on the mass of the mixture. The mixture was sonicated at 350W for 45 min to obtain a composite conductive coating solution.
[0138] (1.4) Copper foil electrodes (3 mm wide and 0.05 mm thick) are pre-embedded in the CS-CF structure carrier layer at equal intervals (100 mm) along the arm axis. The two ends of the electrodes are led out to the connector at the root of the arm. The composite conductive coating liquid is then coated on the CS-CF structure carrier layer with a thickness of 50 μm. It is pre-cured at 100°C for 15 min and then cured at 140°C for 45 min to obtain the CNF / PEDOT conductive sensing layer.
[0139] Experimental Example 1
[0140] The finished products obtained in Examples 1-3 and Comparative Examples 1-5 were tested for flexural strength, interlaminar shear strength, and simply supported beam impact strength. The testing methods are as follows:
[0141] The specimens of Examples 1-3 and Comparative Examples 1-5 were prepared according to GB / T 3354-2014 "Test Method for Tensile Properties of Directed Fiber Reinforced Polymer Matrix Composites", JC / T 773-2010 "Determination of Interlaminar Shear Strength of Fiber Reinforced Plastics by Short Beam Method", and GB / T1451-2005 "Test Method for Impact Toughness of Fiber Reinforced Plastics by Simply Supported Beam Method". The flexural strength was tested by three-point bending on a universal testing machine (Instron 5982, 100kN) with a span-to-thickness ratio of 16:1 and a loading rate of 2mm / min. The interlaminar shear was tested using the short beam method. The impact specimen size was 55×6×4mm, and the test was conducted using a simply supported beam impact testing machine (XJJ-50).
[0142] Table 1. Mechanical property test results of Examples 1-3 and Comparative Examples 1-5
[0143]
[0144] See Figure 1-3 , Figure 1 The image shows the SEM morphology of the CNF / PEDOT conductive sensing layer in Example 3, revealing a uniform coating of cellulose entanglement network and PEDOT conductive phase. This demonstrates its microscopic mechanism as a strain-sensing framework. The CNF / PEDOT conductive sensing layer enhances coating cohesion through the cellulose network, while the uniform distribution of the PEDOT conductive phase avoids localized stress concentration. These two elements synergistically improve the interfacial bonding between the coating and the substrate, reduce crack initiation and propagation, enhance the coating's bending resistance, and lower the risk of cracking and detachment under repeated deformation. This allows the conductive sensing coating to maintain good mechanical stability while achieving its conductive function.
[0145] Figure 2 The image shows the cross-sectional SEM morphology of the biochar electromagnetic shielding layer in Example 3. It shows that the biochar particles are monodisperse in the epoxy matrix and have a dense interface without agglomeration. This reduces the porosity and stress concentration defects caused by agglomeration, improves the bonding state of the filler-matrix interface, effectively transfers load, alleviates the mechanical attenuation caused by filler doping, and allows the tensile, bending and simply supported beam impact properties of the composite material to be well preserved, ensuring the load-bearing and impact resistance required by the UAV arm.
[0146] Figure 3 The image shows the overall cross-sectional SEM morphology of the composite material in Example 3, which shows that the three layers are stacked sequentially from the outside to the inside with good interfacial bonding, further improving the mechanical properties of the composite material.
[0147] Based on the experimental results in Table 1, this invention utilizes a CS-CF structural bearing layer prepared from a combination of cellulose and epoxy resin to withstand the tensile, bending, and torsional loads of the drone arm. Simultaneously, copper foil electrodes are pre-embedded in the CS-CF structural bearing layer, followed by a composite conductive coating. This overcomes the shortcomings of traditional external strain gauges bonded to the drone arm surface, where the bonding layer is susceptible to vibration and temperature / humidity cycles, resulting in high detection limits, difficulty in capturing minute deformations, and susceptibility to electromagnetic interference, leading to decreased measurement reliability. This invention combines biochar powder and epoxy resin, effectively preserving the tensile, bending, and simply supported beam impact properties of the composite material, ensuring the required load-bearing and impact resistance of the drone arm. Combining these three materials at different thicknesses improves the mechanical properties of the composite material, thereby extending the service life of the drone.
[0148] Experimental Example 2
[0149] The finished products of Examples 1-3 and Comparative Examples 1 and 4-5 were subjected to sheet resistance and strain sensitivity tests, and the testing methods are as follows:
[0150] Referring to the four-probe method in GB / T 15662 "Test Method for Volume Resistivity of Conductive and Antistatic Plastics", the RT-70C four-probe tester was used for testing. The probe spacing was 1 mm, and 5 points were measured for each sample. The average value was recorded as the test result.
[0151] The drone arm was fixed to a universal testing machine, and the free end was gradually loaded with 0~50N (in 5N steps). The strain of the ADS1256 resistor and the external reference strain gauge (BF120-3AA) were recorded simultaneously. The fitted values were R / R0=1+GF·ε+kε², and GF=(ΔR / R0) / ε.
[0152] Table 2 Test results of the examples and comparative examples
[0153]
[0154] Based on the experimental results in Tables 1 and 2, the thickness of the CNF / PEDOT conductive sensing layer of this invention, between 80 and 150 μm, can maintain the sheet resistance of the self-sensing arm of the UAV at 480-520 Ω / sq and the interlayer shear strength at 27-28 MPa, thus balancing mechanical properties, conductive continuity, and strain sensitivity.
[0155] In Comparative Example 1, adjusting the arrangement order of the biochar electromagnetic shielding layer and the CNF / PEDOT conductive sensing layer resulted in a significant decrease in the bending strength and strain sensitivity of the finished product. This is likely because changing the arrangement order alters the bonding effect between the composite material and the UAV arm and substrate. Under bending loads, the composite material is prone to microcracks, inducing local debonding of the CNF / PEDOT conductive sensing layer. Simultaneously, the interfacial compatibility between the two functional coatings deteriorates, increasing defects and causing a significant reduction in the bending strength of the component. Furthermore, the deterioration of the interfacial compatibility between the two functional coatings, with increased interfacial pores and microcracks, makes it difficult for the bending strain generated by the substrate to be fully transmitted to the PEDOT sensing phase, resulting in some stress dissipation at the interface. Effective reconstruction of the conductive network during deformation is suppressed, leading to a decrease in strain sensitivity.
[0156] In Comparative Example 4, increasing the thickness of the CNF / PEDOT conductive sensing layer significantly reduced the sheet resistance. This may be because the high redundancy of the conductive network suppresses the relative change in resistance under deformation, thus decreasing strain detection sensitivity. More importantly, this is superior to increasing the thickness of the conductive coating, which allows for the accumulation of greater residual internal stress during the coating curing process. When the component is subjected to interlaminar shear loads, microcracks preferentially form at the high-stress coating-substrate interface. These cracks extend along the bond between PEDOT:PSS and cellulose, inducing microdelamination of the surface layer and causing a significant decrease in interlaminar shear strength.
[0157] In Comparative Example 5, reducing the thickness of the CNF / PEDOT conductive sensing layer resulted in a significant increase in sheet resistance compared to the embodiment. This may be because the reduced conductive phase content in the CNF / PEDOT conductive sensing layer makes it difficult to form a continuous conductive network, reducing the number of conductive pathways and causing some pathways to be interrupted. The limited connection paths for charge conduction decrease the in-plane conductivity of the film, leading to an increase in sheet resistance and a decrease in strain sensitivity.
[0158] Experimental Example 3
[0159] The electromagnetic shielding effectiveness of the finished products from Examples 1-3 and Comparative Examples 1-3 was tested using the following methods:
[0160] Referring to SJ 20524-1995 "Method for measuring the shielding effectiveness of materials", a vector network analyzer (Keysight N5227B, 10MHz~67GHz) was used. The samples of Examples 1-3 and Comparative Examples 2-3 were placed in the WR-90 waveguide section, and the frequency was swept from 8 to 18GHz, with SE=20lg(|E0| / |E1|).
[0161] Table 3. Test results for the examples and comparative examples.
[0162]
[0163] Experimental results show that the thickness of the biochar electromagnetic shielding layer of this invention, which is 200~300μm, can balance the mechanical properties and electromagnetic protection performance of the composite material.
[0164] In Comparative Example 2, adjusting the thickness of the biochar electromagnetic shielding layer to 150 μm resulted in a significant decrease in the electromagnetic protection performance of the finished product. This may be because the biochar phase content within the biochar electromagnetic shielding layer decreased, making it difficult to form a complete conductive network and weakening the reflection effect on electromagnetic waves. Simultaneously, there were insufficient sites for electromagnetic wave absorption and multiple scattering, leading to reduced absorption loss and allowing more electromagnetic waves to directly penetrate the coating, ultimately resulting in a decrease in electromagnetic shielding effectiveness.
[0165] In Comparative Example 3, adjusting the thickness of the biochar electromagnetic shielding layer to 350 μm resulted in a significant decrease in the electromagnetic protection performance of the finished product. This may be because the residual stress increases during the curing process, making the composite material prone to pores and microcracks, which disrupt the continuity of the biochar conductive network and cause local interruptions in conductive pathways. Pore defects also reduce electromagnetic wave absorption loss, and some electromagnetic waves are transmitted through the defects, ultimately leading to a decrease in electromagnetic shielding effectiveness instead of an increase.
[0166] Test Example 4
[0167] The finished product obtained in Example 3 was tested for its temperature and humidity cycling stability and fatigue life. The test methods are as follows:
[0168] Temperature and humidity cycling stability: The finished product was placed in a constant temperature and humidity chamber (ESPEC SH-661) at 85℃ / 85%RH for 1000h. Sheet resistance and strain sensitivity GF were measured every 168h (test method refers to Test Example 2), and the sheet resistance drift rate was calculated.
[0169] Shear resistance drift rate (%) = (Rs) t -Rs0) / Rs0×100%
[0170] Rs t The sheet resistance was measured during the experiment, and Rs0 is the initial sheet resistance.
[0171] Fatigue life: The specimens of Example 3 were tested using an electromagnetic vibration table (LDS V964) at ±5g acceleration for 10 hours. 6 In the next cycle, monitor whether the sensing layer has delaminated.
[0172] Experimental Results: The finished product obtained in Example 3 showed a square resistance drift of 5.3% and a strain sensitivity GF > 9.5 in the temperature and humidity cycling stability test, after 10 cycles under ±5g acceleration. 6 No delamination was observed during the repeated testing cycles. This indicates that the composite material prepared in this invention can extend the service life of the self-sensing arm of a self-contained unmanned aerial vehicle (UAV).
[0173] Finally, it should be noted that the above descriptions are merely preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a composite material for a self-sensing arm of a self-contained unmanned aerial vehicle (UAV), characterized in that, Includes the following steps: (1) Preparation of CS-CF structural bearing layer (1.1) Add urea and cellulose to sodium hydroxide aqueous solution at a mass ratio of 2.5-3.5:1, and control the mass concentration of cellulose in the system to be 8-12%; stir and dissolve at a temperature of -8~-2℃ for 3.5-4.5h to obtain cellulose spinning solution; (1.2) The cellulose spinning solution is extruded into the coagulation bath through a spinneret, and the raw fiber is obtained after coagulation; (1.3) The precursor fiber is pre-oxidized in air at a temperature of 1-3℃ / min to 240-280℃ and held for 40-50min; Subsequently, under nitrogen protection, the temperature was increased to 800-900℃ at 3-7℃ / min for carbonization, and held for 10-20min to obtain CS-CF precursor fiber; (1.4) The CS-CF precursor fibers are impregnated with a resin matrix and woven into a unidirectional fabric, then cured to obtain the CS-CF structural bearing layer; (2) Fabrication of CNF / PEDOT conductive sensing layer (2.1) Cellulose was oxidized by TEMPO and then homogenized under high pressure to obtain CNF dispersion; (2.2) Mix PEDOT:PSS aqueous solution and CNF dispersion at a mass ratio of 4-6:1, add silane coupling agent, mix, and obtain composite conductive coating solution; (2.3) The composite conductive coating liquid is coated on the surface of the CS-CF structure carrier layer, pre-cured at 90~110℃ for 10-20min, and then cured at 130~150℃ for 45min to obtain CNF / PEDOT conductive sensing layer. (3) Preparation of biochar electromagnetic shielding layer A biochar electromagnetic shielding layer was prepared by mixing biochar powder and epoxy resin in a mass ratio of 15~30:70~85. (4) The CNF / PEDOT conductive sensing layer and the biochar electromagnetic shielding layer are stacked in sequence, placed in a vacuum bag and cured by hot pressing to obtain a composite material for the self-sensing arm of the unibody UAV.
2. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (1.4), by weight, the raw materials of the resin matrix include 90-110 parts of mixed epoxy resin, 8-12 parts of DOPO flame retardant, and 27-33 parts of lignin-based curing agent. The resin content of the unidirectional fabric is 33-37%, and the areal density is 190-210 g / m². The curing process involves placing the unidirectional fabric in a vacuum bag, evacuating it, sealing it, and then placing it in an autoclave. The temperature is increased to 140-160°C at a rate of 1-3°C / min, while the pressure is increased to 0.5-0.7 MPa. The temperature and pressure are maintained for 80-100 min. Subsequently, the temperature is decreased to 60°C at a rate of 0.7-1.5°C / min, and the pressure is released from the autoclave.
3. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (2.1), the TEMPO oxidation is performed using sodium hypochlorite as the oxidant, with a sodium hypochlorite dosage of 3-7 mmol / g. The high-pressure homogenization treatment is performed at a pressure of 75-85 MPa, with 2-4 treatment cycles. The CNF dispersion has a solid content of 1.8-2.2%.
4. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (2.2), the silane coupling agent is KH-560, and the dosage is 0.8-1.2%. The mixing is performed by ultrasonication at 300-400W for 40-50 minutes. In step (2.3), the coating thickness of the composite conductive coating liquid is 80-150μm.
5. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (3), the method for preparing the biochar powder includes the following steps: S1: Gasify cotton stalks at 780-850℃ for 55-65 minutes to obtain crude biochar; S2: The crude biochar was ball-milled using zirconia balls as the milling medium at a ball-to-material ratio of 8-12:1, a milling speed of 280-320 rpm, and a milling time of 1.5-2.5 h. The powder with a particle size of 20-40 μm was obtained by passing it through a 400-mesh sieve and modifying it with KH-560 silane coupling agent to obtain biochar powder.
6. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (3), the raw material of the biochar electromagnetic shielding layer, based on the weight of epoxy resin, also includes 20-30% amine curing agent. The mixing is performed by mixing the raw material of the biochar electromagnetic shielding layer using a planetary stirring method. The vacuum degree of the planetary stirring is -0.08~-0.1MPa, the rotation speed is 50-70rpm, the stirring time is 20-40min, and the thickness of the biochar electromagnetic shielding layer is 200~300μm.
7. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 2, characterized in that, The mixed epoxy resin is epoxy resin E-51 and epoxy resin F-51 in a mass ratio of 60~80:20~40, and the preparation method of the lignin-based curing agent includes the following steps: A1: Phenolicizing lignin to obtain phenolized lignin. The conditions for the phenolicizing reaction are: a mass ratio of phenol to lignin of 2-4:1, a molar ratio of formaldehyde to phenol of 0.5-1.0:1, oxalic acid or hydrochloric acid as the catalyst, a reaction temperature of 70-90℃, and a reaction time of 2-4h. A2: Phenolic lignin is dissolved in N,N-dimethylformamide, DOPO, formaldehyde and catalyst are added, and the mixture is stirred and mixed at 100~140℃ for 3~6h to obtain a reaction solution. The reaction solution is added to deionized water to precipitate, filtered, washed with water and vacuum dried to obtain a lignin-based curing agent.
8. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 7, characterized in that, The ratio of phenolic lignin to N,N-dimethylformamide in the liquid solution is 1g:4-6mL, the mass ratio of DOPO flame retardant to phenolic lignin is 0.4-0.8:1, the molar ratio of formaldehyde to DOPO flame retardant is 1.0-2.0:1, the catalyst is triethylamine or sodium hydroxide, and the amount of catalyst used is 1%-3% of the total mass of the reactants.
9. The method for preparing the composite material for the self-sensing arm of a self-contained unmanned aerial vehicle according to claim 1, characterized in that, In step (4), the curing process is as follows: the temperature is raised to 120-150℃ at a heating rate of 1-2℃ / min, the curing pressure is 0.3-0.6MPa, and the temperature and pressure are maintained for 60-120min.
10. A composite material for a self-sensing arm of a self-contained unmanned aerial vehicle, characterized in that, It is prepared by any one of the preparation methods of claims 1-9.
